Delayed medical consultation and influencing factors in elderly patients with obstructive sleep apnea syndrome - Sun, Qihui; Shi, Xiaoying (Frontiers in Medicine, 2025)
ObjectiveThis study aims to examine the prevalence of delays in medical consultation and the associated factors among elderly patients with obstructive sleep apnea syndrome (OSA) through a cross-sectional survey design.MethodsA total of 276 elderly OSA patients were recruited from the sleep monitoring unit of a tertiary hospital in Shanghai, following overnight assessment with the Apnealink portable monitoring device between 2021 and 2022. Data were collected through a general demographic questionnaire, the OSA Knowledge, Attitude, and Practice (KAP) questionnaire, the Perceived Barriers to Medical Consultation Scale, and the Life Satisfaction Scale to evaluate medical consultation delays and their correlates.ResultsAmong the 276 elderly OSA patients included in the analysis, the shortest recorded delay in seeking medical attention was 0.20 years, while the longest exceeded 40 years, demonstrating that all patients experienced some degree of delay, with a 100% incidence rate. Factors influencing medical consultation delays were identified in the following order: perceived barriers to medical consultation, levels of KAP, clinical symptoms such as excessive daytime sleepiness and morning xerostomia, life satisfaction, and the method of healthcare payment.ConclusionElderly OSA patients mainly with a secondary or higher education and moderate- or high-income universally face varying degrees of delays in seeking medical care, reflecting an overall concerning trend in healthcare engagement. It is imperative for healthcare professionals to conduct regular health education initiatives aimed at the elderly population to enhance awareness of OSA, foster a proactive approach to seeking medical care, and promote accurate disease comprehension, thereby improving the likelihood of timely consultation.